STRATEGI PEMASARAN DIGITAL BAGI UMKM DI JEMBER: ADAPTASI DAN TANTANGAN - Wilaga, Brian Adi; Qomariah, Nurul; Nursaid, Nursaid (Fakultas Ekonomi dan Bisnis, 2025)
UMKM in Jember have a strategic role in the local economy, but face challenges in competition in the digital era. This research analyzes the digital marketing strategies implemented by UMKM in Jember as well as the obstacles and opportunities they face. Using qualitative descriptive methods, data was collected through observation, interviews and documentation. The research results show that UMKM in Jember are starting to utilize social media such as Instagram and TikTok, as well as marketplaces such as Shopee and Tokopedia to expand their market reach. However, the main challenges faced include low digital literacy, limited capital, intense competition on digital platforms, and changes in social media algorithms. To overcome this obstacle, UMKM implement adaptation strategies such as digital marketing training, collaboration with micro-influencers, and marketing diversification between online and offline. This study concludes that digital marketing can increase the competitiveness of UMKM, but it needs support from the government and the business community to ensure its sustainability and effectiveness.